J-fractional regularization of linear ill-posed equations - Syavavko, M. S. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We present a method for solution of linear ill-posed equations in function spaces based on the use of continuous J-fractions. We obtain a meromorphic solution of regularized equations and indicate some cases where a solution can be represented in terms of rational functions.